2018
DOI: 10.4149/neo_2018_180122n47
|View full text |Cite
|
Sign up to set email alerts
|

The expression of clock genes cry1 and cry2 in human colorectal cancer and tumor adjacent tissues correlates differently dependent on tumor location

Abstract: Colorectal cancer (CRC) exhibits differences in its features depending on the location of the tumor. The role of the circadian system in carcinogenesis is accepted, and many studies report different clock gene expression in tumors compared to healthy tissue. However, little attention is given to the changes in clock genes in tumors arising from various locations across the colon and rectum. The aim of our study was to investigate the expression of the clock genes cry1 and cry2 in human CRC tissue and tissue ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 30 publications
(42 reference statements)
0
10
0
Order By: Relevance
“…Further evidence has indicated that Cry2 suppresses colon tumour growth, but the role of Cry1 in cancer progression remains controversial. Compared to matched normal mucosa, gene expression of Cry1 was reported to be upregulated in colon carcinoma tissues by three studies ( 37 , 72 , 73 ), but two other studies claimed that the expression of Cry1 did not differ significantly between groups ( 39 , 46 ). Cry2 was identified to be downregulated in CRC tissues in three studies ( 37 , 39 , 50 , 72 ).…”
Section: Associations Between Crc and Circadian Clock Genesmentioning
confidence: 99%
“…Further evidence has indicated that Cry2 suppresses colon tumour growth, but the role of Cry1 in cancer progression remains controversial. Compared to matched normal mucosa, gene expression of Cry1 was reported to be upregulated in colon carcinoma tissues by three studies ( 37 , 72 , 73 ), but two other studies claimed that the expression of Cry1 did not differ significantly between groups ( 39 , 46 ). Cry2 was identified to be downregulated in CRC tissues in three studies ( 37 , 39 , 50 , 72 ).…”
Section: Associations Between Crc and Circadian Clock Genesmentioning
confidence: 99%
“…Recent study examining the role of PER3 in CRC found that its overexpression enhanced fluorouracil sensitivity in CRC cells, proposing it as a potential target in CRC treatment (243). Moreover, another study showed sex-specific expression and sex-specific prognostic value of clock and clock-controlled genes, shedding light on colorectal cancer and patient characteristics that have to be taken into consideration in order to provide optimal treatment (244).…”
Section: New Therapeutic Strategiesmentioning
confidence: 99%
“…The low rate of ADCYAP1 hypermethylation in early-stage lesions and its increase with the tumor stage suggest that ADCYAP1 hypermethylation may hinder ADCYAP1's apoptotic action. Cry1 expression was increased in right colon cancers but not in left colorectum tumors [ 33 ]. CRY2NK1 upregulation is associated with a worse outcome in patients with hepatocellular cancer.…”
Section: Discussionmentioning
confidence: 99%